Early management of acute severe UC in the biologics era: development and international validation of a prognostic clinical index to predict steroid response. Issue 3 (28th September 2022) - Adams, Alex; Gupta, Vipin; Mohsen, Waled; Chapman, Thomas P; Subhaharan, Deloshaan; Kakkadasam Ramaswamy, Pradeep; Kumar, Sudheer; Kedia, Saurabh; McGregor, Colleen GC; Ambrose, Tim; George, Bruce D; Palmer, Rebecca; et al.
Abstract : Objectives: We aimed to determine whether changes in acute severe colitis (ASC) management have translated to improved outcomes and to develop a simple model predicting steroid non-response on admission. Design: Outcomes of 131 adult ASC admissions (117 patients) in Oxford, UK between 2015 and 2019 were compared with data from 1992 to 1993. All patients received standard treatment with intravenous corticosteroids and endoscopic disease activity scoring (Ulcerative Colitis Endoscopic Index of Severity (UCEIS)). Steroid non-response was defined as receiving medical rescue therapy or surgery. A predictive model developed in the Oxford cohort was validated in Australia and India (Gold Coast University Hospital 2015–2020, n=110; All India Institute of Medical Sciences, New Delhi 2018–2020, n=62). Results: In the 2015–2019 Oxford cohort, 15% required colectomy during admission vs 29% in 1992–1993 (p=0.033), while 71 (54%) patients received medical rescue therapy (27% ciclosporin, 27% anti-tumour necrosis factor, compared with 27% ciclosporin in 1992–1993 (p=0.0015). Admission C reactive protein (CRP) (false discovery rate, p=0.00066), albumin (0.0066) and UCEIS scores (0.015) predicted steroid non-response. A four-point model was developed involving CRP of ≥100 mg/L (one point), albumin of ≤25 g/L (one point), and UCEIS score of ≥4 (1 point) or ≥7 (2 points). Patients scoring 0, 1, 2, 3 and 4 in the validation cohorts had steroid response rates of 100, 75.0%, 54.9%, 18.2% and 0%, respectively. Scoring of ≥3 was 84% (95% CI 0.70 to 0.98) predictive of steroid failure (OR 11.9, 95% CI 10.8 to 13.0). Colectomy rates in the validation cohorts were were 8%–11%. Conclusions: Emergency colectomy rates for ASC have halved in 25 years to 8%–15% worldwide. Patients who will not respond to corticosteroids are readily identified on admission and may be prioritised for early intensification of therapy.